Dithiolate and diselenolate complexes [Pt2(μ-ECH2CH{double bond, long}CHCH2E)(PPh3)4]2+ (E = S, Se): Synthesis, characterisation and mass spectrometric formation of the dichalcogenide species [Pt2(μ-E2)(PPh3)4]2+ - Devoy, S.M. (2014)
10.1016/j.ica.2008.06.005